The Bloomsbury research handbook of Indian philosophy and gender - Howard, Veena (Bloomsbury research handbooks in Asian philosophy., 2020)
'How do gender constructions transform religious experiences?' 'What is the role of bodily materiality in ethics and epistemology?' 'How does rethinking gender and sexuality force us to reconceptualise settled ontological frameworks?' This collection provides the first research resource to Indian philosophical gender issues, exploring a variety of texts and traditions from Indian philosophy where the treatment of gender is dynamic and diverse.Organised around three central themes - the gender dynamics of enlightenment in the Hindu and Buddhist traditions; the simple binary opposition of genders in Indian traditions; the ways in which symbolic representations of gender differ from social realities in Hindu and Buddhist practice - a team of respected scholars discuss feminist readings, examinations of femininity and masculinity, as well as queer and trans identities, representations, and theories. Beginning with the Vedic tradition and ending with sections on Sri Ramakrishna and Gandhi, this wide-ranging handbook encourages fresh inquiry into classic philosophical questions. Offering critical analyses relevant to literary, cultural and religious studies, The Bloomsbury Research Handbook of Indian Philosophy and Gender opens up new ways of understanding gender and South Asian philosophy